Examining relationships between age at diagnosis and health-related quality of life outcomes in prostate cancer survivors - Christine J. Kurian; Amy E. Leader; Melissa S. Y. Thong; Scott W. Keith; Charnita M. Zeigler-Johnson (BMC, 2018)
Abstract Background Patient reports of health related quality of life can provide important information about the long-term impact of prostate cancer. Because patient symptoms and function can differ by age of the survivor, the aim of our study was to examine patient-reported quality of life and prostate symptoms by age at diagnosis among a registry of Dutch prostate cancer survivors. Methods A population of 617 individuals from the Patient Reported Outcomes Following Initial Treatment and Long-Term Evaluation of Survivorship (PROFILES) database was surveyed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC-QLQ-C30) and prostate symptom (EORTC QLQ-PR25) scales. Age at diagnosis was the main independent variable, with three age categories: 60 years and younger, 61-70 years, and 71 years and older. Dependent variables were the EORTC-QLQ-C30 and EORTC QLQ-PR25 scales, divided into positive and negative outcomes. Positive measures of health-related quality of life included global health, physical functioning, role functioning, emotional functioning, cognitive functioning, and social functioning. Negative outcomes included fatigue, nausea, pain, dyspnea, insomnia, appetite, constipation, and diarrhea. We also assessed sexual activity, and urinary, bowel and hormonal symptoms. Descriptive analyses included frequencies with chi-square tests and medians with Kruskal-Wallis tests. Multivariable adjusted analyses were conducted by median regression modeling. Results Among the numerous scales showing some unadjusted association with age group, only two scales demonstrated significant differences between prostate cancer patients age 71+ compared to the youngest group (age < 61) after multivariable adjustment. On average, the oldest patients experienced an 8.3-point lower median physical functioning score (β = − 8.3; 95% CI = − 13.9, − 2.8; p = 0.003) and a 16.7-point lower median sexual activity score (β = − 16.7; 95% CI = − 24.7, − 8.6; p < 0.001) while controlling for BMI, marital status, time since diagnosis, comorbidities (heart condition), Gleason score, and treatment (prostatectomy). Conclusions Results suggest that patient age at diagnosis should be considered among factors that contribute to health-related quality of life outcomes for prostate cancer survivors. Implications for Cancer Survivors: A possible reevaluation of screening recommendations may be appropriate to acknowledge age as a factor contributing to health-related quality of life outcomes for prostate cancer survivors.